Children's Voice in "Nurseries of Democracy". Participation in Early Childhood Institutions - Alexandra Klein; Sandra Landhäußer (Social Work & Society, 2018)
According to the UN Conventions on the Rights of the Child all children have a right to participation. This UN Convention has influenced professionals and policy-makers worldwide. Thereby participation in kindergarten refers to children's possibilities to exercise influence on a range of topics from the rules that are applied in the nursery's course of a day, the daily program, the interior design of the facility, etc. Which possibilities for participation children actually have in their everyday lives and how they perceive these possibilities has not been sufficiently answered in the international discourse. Based on a standardized survey with 4 and 5 year old children on their experiences with various aspects of participation in pre-school institutions the paper contributes to international childhood and participation research. The empirical findings are related to the democracy-theoretical inspired figures of early childhood institutions as "nurseries of democracy" and broader reflections on social inequalities in early childhood.